2005
DOI: 10.1152/ajpregu.00862.2004
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human pregnancy on the ventilatory chemoreflex response to carbon dioxide

Abstract: This study examined the effects of human pregnancy on the central chemoreflex control of breathing. Subjects were two groups ( n = 11) of pregnant subjects (PG, gestational age, 36.5 ± 0.4 wk) and nonpregnant control subjects (CG), equated for mean age, body height, prepregnant body mass, parity, and aerobic fitness. All subjects performed a hyperoxic CO2 rebreathing procedure, which includes prior hyperventilation and maintenance of iso-oxia. Resting blood gases and plasma progesterone and estradiol concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
2
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 32 publications
1
55
2
2
Order By: Relevance
“…In this study and in studies in humans, increases in the rate of inspiration during pregnancy reflect an increased respiratory drive (Kolarzyk et al, 2005). In humans, at least, this increase in the rate of inspiration during pregnancy may be associated with overcoming increased respiratory system resistance (Kolarzyk et al, 2005) and/or may be linked with progesterone-associated changes in central chemosensitivity (Jensen et al, 2005). It is likely that lung compression during pregnancy in T. rugosa decreases lung compliance and an increase in the rate of inspiration may be an advantageous compensatory response.…”
Section: Breathing Patterns During Gestationmentioning
confidence: 49%
“…In this study and in studies in humans, increases in the rate of inspiration during pregnancy reflect an increased respiratory drive (Kolarzyk et al, 2005). In humans, at least, this increase in the rate of inspiration during pregnancy may be associated with overcoming increased respiratory system resistance (Kolarzyk et al, 2005) and/or may be linked with progesterone-associated changes in central chemosensitivity (Jensen et al, 2005). It is likely that lung compression during pregnancy in T. rugosa decreases lung compliance and an increase in the rate of inspiration may be an advantageous compensatory response.…”
Section: Breathing Patterns During Gestationmentioning
confidence: 49%
“…Withdrawal of these hormones would therefore be expected to decrease resting V E, thereby increasing Pa CO 2 in otherwise healthy postmenopausal women. Although the underlying mechanisms of these ventilatory adaptations remain speculative, the combined facilitatory effects of P 4 and E 2 on central and/or peripheral chemoreflex drives to breathe may be involved (3,4,11,26,28,29,31,48 (18 -21), this is the first study to examine the role of acid-base balance in the chemoreflex control of breathing in healthy postmenopausal women.In the present study, we postulated that reductions in circulating female sex hormone concentrations, alone or in combination with the alkalizing effect of an increased plasma [SID], contribute significantly to the relative hypoventilation and attendant arterial hypercapnia observed after the onset of menopause. We hypothesized that these outcomes would be mechanistically linked to reductions in central and peripheral chemoreflex drives to breathe.…”
mentioning
confidence: 95%
“…
(25,28,40,48,51,54). Hormone replacement therapy studies reported that medroxyprogesterone acetate (a synthetic progestin), administered alone and in combination with E 2 , consistently reduced resting Pa CO 2 by ϳ6 mmHg in postmenopausal women (39,(43)(44)(45)(46).
…”
mentioning
confidence: 99%
“…As a consequence, maternal arterial pH is increased to 7.46. The increased respiratory effort and decrease in PCO 2 has been related to progesterone and to a lesser degree to estrogen (Wolfe et al 1998, Jensen et al 2005.…”
Section: The Respiratory Systemmentioning
confidence: 99%